2004
DOI: 10.1242/jeb.00771
|View full text |Cite
|
Sign up to set email alerts
|

The binding and recall of snapshot memories in wood ants (Formica rufaL.)

Abstract: snapshot recall, provided that the components of a snapshot are bound together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 17 publications
(18 reference statements)
0
29
0
Order By: Relevance
“…Path integration is of limited precision and as a foraging ant repeats a PI-derived path to and from a reliable foraging location, it rapidly becomes familiar with the landscape and forms long-term view-based memories that both specify the exact route (Collett, 2010;Collett et al, 1992;Cornetz, 1910;Graham et al, 2003;Harris et al, 2007;Narendra et al, 2013) and act as an attractor, guiding ants to a familiar goal (Åkesson and Wehner, 2002;Graham et al, 2004;Wystrach et al, 2012). Ants can also form vector memories of route segments, instead of the whole route from feeder to the nest (C. fortis: Collett and Collett, 2009;Collett et al, 1998;; Apis mellifera: Collett et al, 2002;Srinivasan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Path integration is of limited precision and as a foraging ant repeats a PI-derived path to and from a reliable foraging location, it rapidly becomes familiar with the landscape and forms long-term view-based memories that both specify the exact route (Collett, 2010;Collett et al, 1992;Cornetz, 1910;Graham et al, 2003;Harris et al, 2007;Narendra et al, 2013) and act as an attractor, guiding ants to a familiar goal (Åkesson and Wehner, 2002;Graham et al, 2004;Wystrach et al, 2012). Ants can also form vector memories of route segments, instead of the whole route from feeder to the nest (C. fortis: Collett and Collett, 2009;Collett et al, 1998;; Apis mellifera: Collett et al, 2002;Srinivasan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory and field studies using artificial landmarks at the nest (Wehner and Räber, 1979;Wehner et al, 1996;Akesson and Wehner, 2002;Narendra et al, 2007) or a feeder (Wolf and Wehner, 2000;Durier et al, 2003;Graham et al, 2004) have shown how visual landmark information can be used to guide the search for an important location. The basic mechanism is for a single view of the world to be stored at the goal location.…”
Section: Introductionmentioning
confidence: 99%
“…A second way that snapshot memories could be used is known as retinal image matching (9). For this mechanism, a view along a route would trigger the snapshot memory that had been acquired at a nearby location, and the individual would move until its view matched the retinal positions and sizes of the features in the remembered snapshot (23). A route would then be encoded as a set of snapshotdefined locations, each of which would act as an attractor from nearby positions (Fig.…”
mentioning
confidence: 99%